Possibilities and Practical Experiences of Using Artificial Intelligence in Taxation - Szabó, Ildikó (Pázmány Law Review, 2025)
The present paper aims at analysing whether or not AI/robots should be taxed to counter this backdrop. In the first part, the author summarizes selected targeted options that have been considered for taxing AI/robots. The author also analyses the various options from the perspective of relevant tax policy principles. In light of the assessment and discussion in the article, the author puts forward the idea of a sovereign measure, that is, an education tax. Moreover, given the fact that a sovereign measure may not be sufficient to tackle the issue at stake, the author discusses the possibility of implementing a global fiscal redistribution mechanism (multilateral solution) from developed (surrender jurisdictions) to developing countries (recipient jurisdictions). One such solution is to create a global education tax to foster education or awareness in developing or low-income countries. A much broader solution would be to introduce the so-called planetary tax, which would assist developing or low-income countries in dealing with a wide range of planetary issues.